An evaluation of the physiological demands of elite Rugby Union using global positioning system tracking software - Cunniffe, B.; Proctor, W.; Baker, J. S.; Davies, B. (The Journal of Strength and Conditioning Research, 2009)
The current case study attempted to document the contemporary demands of elite rugby union. Players (n = 2) were tracked continuously during a competitive team selection game using Global Positioning System (GPS) software. Data revealed that players covered on average 6,953 m during play (83 minutes). Of this distance, 37% (2,800 m) was spent standing and walking, 27% (1,900 m) jogging, 10% (700 m) cruising, 14% (990 m) striding, 5% (320 m) high-intensity running, and 6% (420 m) sprinting. Greater running distances were observed for both players (6.7% back; 10% forward) in the second half of the game. Positional data revealed that the back performed a greater number of sprints (>20 km/h) than the forward (34 vs. 19) during the game. Conversely, the forward entered the lower speed zone (6-12 km/h) on a greater number of occasions than the back (315 vs. 229) but spent less time standing and walking (66.5 vs. 77.8%). Players were found to perform 87 moderate-intensity runs (>14 km/h) covering an average distance of 19.7 m (SD = 14.6). Average distances of 15.3 m (back) and 17.3 m (forward) were recorded for each sprint burst (>20 km/h), respectively. Players exercised at ~80 to 85% Vo2max during the course of the game with a mean heart rate of 172 b/min (~88% HRmax). This corresponded to an estimated energy expenditure of 6.9 and 8.2 MJ, back and forward, respectively. The current study provides insight into the intense and physical nature of elite rugby using on the field assessment of physical exertion. Future use of this technology may help practitioners in design and implementation of individual position-specific training programs with appropriate management of player exercise load.